Mechanical behaviour and fracture toughness evaluation of rubber toughened polypropylene nanocomposites - Lim, Jian Wei; Hassan, Azman; Rahmat, Abd Razak; Wahit, Mat Uzir (Maney Publishing, 2006)
Rubber toughened polypropylene (PP) nanocomposites (RTPPNC) containing organophilic layered silicates were prepared by means of melt extrusion at 230Â°C using a co-rotating twin-screw extruder in order to examine the influence of the organoclay and polyethylene octene (POE) as filler and impact modifier, respectively, on mechanical and fracture properties. The mechanical properties of RTPPNC were studied through tensile, flexural and impact tests. The strength and stiffness of RTPPNC were improved significantly with an increase in the clay content, in the presence of maleic anhydride modified PP (PPgMAH). From the tensile and flexural tests, the optimum loading of organoclay in impact modified PP was found to be 6 wt-%. Conversely, the stiffness and strength of the blends decreased with respect to pure PP as the concentration of POE in the blends was increased. The essential work of fracture (EWF) method was also used to evaluate the fracture toughness of the RTPPNC. EWF measurements indicated that the specific essential work of fracture (we) decreased with an increase in the organoclay content. However, additions of POE elastomer are beneficial in enhancing the we of the PP blends. we appeared to increase with increasing POE content up to 20 wt-%.